THE USE OF E-DIARY TO IMPROVE STUDENT’S WRITING SKILL - Abas Oya; Meisyaroh Meisyaroh; Kamsini Kamsini (BAHTRA : Pendidikan Bahasa dan Sastra, 2021)
This journal aims to implement E-diary to improve students’ writing skill. Writing is the most difficult thing to do for most students in the classroom. Students often find difficulties to write their ideas in limited time and the condition of the classroom. Some students were also annoying to their other friends.  To improving the writing skill, It is also needed to practice it routinely.  One of the ways to improve students’ writing skill is E-diary writing. By using E-diary writing, students can practice writing the daily experience routinely whenever and wherever without limiting by the time.  E-diary also can make diary writing more interactive and exciting.